Critics' Corner—Critical Resistance to the Jazz Metaphor - Hatch, Mary Jo; Weick, Karl E. (Organization Science, 1998)
There was a surprising set of reactions when Mary Jo Hatch began talking about jazz on the colloquium circuit soon after the Vancouver concert. She agonized over these reactions in a brief note she sent to the three co-editors. (A revised version appears below.) Upon reading the note, Weick had a quick, reasonably intense “counterpoint” reaction. Hatch's comment appears below. Following that, unedited—just as was the case for Berniker's spontaneous reaction to the symposium—we reproduce Weick's comments to the other two editors upon reading Hatch's note.